(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
This paper demonstrates that according to a consequence of General Theory of Relativity, a high amount of electromagnetic waves, such as ultraviolet light, injected between two or more parallel reflective surfaces must generate through multiple reflections gravitational waves having a significant power which are radiated into space. The emitted gravitational waves have the same frequency as the incident electromagnetic waves and are directed along the normal to the reflective surfaces. This papers derives, an equation connecting the radiated gravitational power with the electromagnetic energy injected between reflective plates. The radiated gravitational power can be enhanced and focused on a point using multiple reflective calottes.